Analysis of the Respiratory Tract Morbidity in Children Living in Big Cities - Trotskyy, Hryhoriy M.; Lisnyy, Andriy Y.; Pakulova-Trotska, Yuliya V.; Kamut, Nataliya V. (International Journal of Child Health and Nutrition, 2021)
Upper and lower respiratory tract pathology is an urgent problem of modern paediatrics since it is the most common paediatric disease. The aim was to conduct a retrospective analysis of the structure of respiratory diseases in children. Materials and methods: We conducted a retrospective analysis of 5,615 medical records of patients undergoing inpatient treatment at the non-profit municipal enterprise City Children's Clinical Hospital in 2018 for respiratory system pathology. Retrospective analysis is performed using the electronic program "Doctor Eleks", which allows us to search and form a group of case histories by keyword. The age characteristics and the structure of the respiratory tract morbidity were defined, seasonal prevalence and duration of treatment, and the medical conditions requiring the longest inpatient treatment were determined. A judicious approach is required to the question of hospitalisation of a patient with respiratory pathology - it must be timely and well-founded because the presence of a respiratory pathology does not always require hospitalisation. There is a necessity in studying the causes of hospitalisation of children for respiratory pathology and retrospectively study the history and causes of re-hospitalisations to develop recommendations for reducing the incidence of hospitalisation. It is also planned to study the structure of hospitalised patients according to other nosologies (pathology of the digestive tract, urinary system, etc.) in the nearest future in order to propose an algorithm for optimising the processes of hospitalisation by differentiating visitors who actually need hospitalisation and those who may be in outpatient treatment.